Enhancement of efficiency and power output of hydrogen fuelled proton exchange membrane (PEM) fuel cell using oxygen enriched air. (19th February 2023) - Kumar, Rohan; Subramanian, K.A.
Abstract: This paper deals with the effects of the oxygen-enriched air (up to 50% oxygen by mass) along with other operating parameters (hydrogen flow rate, temperature, and relative humidity) on the performance of hydrogen-fuelled proton exchange membrane (PEM) fuel cell. The active area of a fuel cell considered was 50 cm 2 with three cells in series connections. The air was supplied with O2 enriched from 23% to 50% at the cathode. The voltage obtained with the respective enriched air was 2.52 and 2.80 V respectively. The optimum oxygen enrichment was found as 45%. The stack temperature plays a significant role on performance improvement and the optimum temperature was found as 50 °C. The voltage efficiency and power output were improved by 9% and 33% with 45% oxygen-enriched air. Electrochemical impedance spectroscopy was used to analyze the impedance behavior of the fuel cell with the variable current demand. The bode plot indicates current dominates voltage at low oxygen-enriched air (25%) and vice-versa at high-enriched air. The inductive effect was dominating at the low frequency and overtaken by the capacitive effects at the higher frequency. These results would be useful to develop a dedicated fuel cell with the oxygen-enriched air. Highlights: Oxygen-enriched air enhances power and efficiency of PEM fuel cell. The voltage efficiency is the highest (by 9%) at 45% oxygen enriched air. Stack temperature rises beyond 50% enriched air. Current dominates voltage at low oxygen enriched air (25%) and viceversa. Inductive effect at low frequency dominates than capacitive effect and viceversa.